Protocol for differentiating hematopoietic progenitor cells from human pluripotent stem cells in chemically defined monolayer culture - Shaokang Mo; Kengyuan Qu; Jun Shen; Kuangyu Yen (STAR Protocols)
Summary: Human pluripotent stem cells (hPSCs) provide a powerful platform for generating hematopoietic progenitor cells (HPCs) and investigating hematopoietic development. Here, we present a protocol for maintaining hPSCs and inducing their differentiation into HPCs through the endothelial-to-hematopoietic transition (EHT) on vitronectin-coated plates. We outline steps for evaluating the efficiency of HPC generation and assessing their potential to differentiate into various hematopoietic lineages. This protocol serves as a framework for exploring human hematopoiesis and generating various functional blood cells.For complete details on the use and execution of this protocol, please refer to Shen et al.1 and Qu et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.